Preparation and characterisation of smart polymer gels for wearable electronics - Shen, Clarence Xuanyi (2018)
Self-healing materials are gaining more attention and recognition over the years due its wide array of usage and huge potential. They allow technological devices to heal physical or mechanical damages, while retaining their electrical properties and original capabilities. In this project, dielectric layer in thin-film transistors is the subject of focus as several compounds were investigated for their potential as a self-healing material for these transistors that can be used in flexible devices or wearable technologies. Here, a compound managed to successfully fabricate thin-film transistors that possess a self-healable dielectric layer and functional Field-Effect Mobility. The dielectric layer that was fabricated with a catechol-group polymer and Ionic Liquid, had shown healing capabilities when placed under conditions at 100°C for 10 minutes. Furthermore, a check on the capacitance value had shown that these dielectric layers functioned at above 1μF/ 2 at 20Hz, which are high capacitance values. Thus, enhancing its feasibility to be used in thin-film transistors.